2019
DOI: 10.3928/01484834-20190819-10
|View full text |Cite
|
Sign up to set email alerts
|

International Service-Learning for Nurse Practitioner Students: Enhancing Clinical Practice Skills and Cultural Competence

Abstract: Background: The purpose of this project was to determine whether an international service-learning nurse-led clinic was a beneficial experience for nurse practitioner (NP) students in improving diagnostic and cultural confidence, skills acquisition, and cultural competence during a clinical practicum. Method: The sample consisted of 10 Doctor of Nursing Practice (DNP) students in various NP tracks during an international service-learning experience in G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Forty-six studies were conducted in the USA, two in Brazil [ 29 , 30 ], one was a joint study between the USA and Haiti [ 31 ], another one between Canada and Colombia [ 32 ], and one study was conducted by USA investigators in Guatemala [ 33 ]. No English language studies were identified from other LAC countries.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Forty-six studies were conducted in the USA, two in Brazil [ 29 , 30 ], one was a joint study between the USA and Haiti [ 31 ], another one between Canada and Colombia [ 32 ], and one study was conducted by USA investigators in Guatemala [ 33 ]. No English language studies were identified from other LAC countries.…”
Section: Resultsmentioning
confidence: 99%
“…A total of six articles focused on preparing nurses of the future through partnerships with colleges of nursing, non-governmental organizations, a local catholic services agency, and an international service-learning nurse-led clinic [ 31 , 33 , 38 , 58 , 61 , 66 ]. Processes involved global service learning, a train-the-trainer approach, provision of primary care by students and faculty, and student volunteer involvement in health promotion and needs assessment [ 31 , 33 , 38 ]. Through a global health immersion course that included an international nurse-led clinic, doctoral nursing students improved not only their clinical diagnostic skills, but also their cultural competence [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bringle, Hatcher, and Jones (2011) defined ISL as a structured academic experience in a different country that typically includes a discipline-specific service activity and cross-cultural interaction, as well as participant reflection on the experience (as cited in Lawson & Olson, 2017). Ford, Neilan, and Moscou (2017) described multiple benefits of ISL in Guatemala among nursing students. Following the ISL experience, students gained a broader perspective of medical, social, and cultural values as well as increased sensitivity to cultural similarities and differences.…”
Section: Literature Review International Service-learning In Medical mentioning
confidence: 99%